Randomized Controlled Trial Evaluating the Efficacy and Cost Effectiveness of a Ready-to-Use Applicator Containing Iodine Povacrylex and Isopropyl Alcohol Compared with Conventional Skin Scrubbing and Painting in Patients Undergoing Colorectal Surgery - Tanjak, Pariyada; Thiengtrong, Benjarat; Lohsiriwat, Darin; Lohsiriwat, Varut; Leelaratsamee, Amorn; Chinswangwatanakul, Vitoon (Siriraj Medical Journal, 2021)
Objective: The aim of this study was to evaluate the efficacy and cost-effectiveness of a ready-to-use applicator containing iodine povacrylex and isopropyl alcohol (IPIA) for the prevention of surgical site infection (SSI) following intra-abdominal surgery. Materials and Methods: The IPIA was randomly used in patients who underwent colorectal surgical procedures. The control group for comparison was a group of patients who underwent colorectal surgical procedures using conventional skin scrubbing and painting with antiseptic solutions without IPIA. In total, 100 patients were included in the study, randomized into 2 groups: one was applied IPIA and another group a conventional skin preparation. The outcome measurements included ease-of-use as assessed by a questionnaire, preparation time comparison, estimated skin preparation expense, adverse reactions, and rate of SSI. All the patients were visited daily up to 7 days postoperation or until discharge, and then 14 and 30 days postoperatively for monitoring the occurrence of SSI. Results: Of the 100 patients undergoing elective intra-abdominal surgery enrolled in the study, 51 were males and 49 females, with the mean age of 63.5 ± 11.3 years. The majority of the patients had undergone colorectal cancer colectomies or rectal resections. There was no mortality. Seven patients (7%) had postoperative SSI (4 patients in the control group and 3 patients in the IPIA group, 4% vs. 3%, p = 0.45). The bacterial cultures revealed Gram negative-bacilli in all of the patients with SSI. The preparation time for the skin preparation was 5.48 ± 2.49 min in the control group and 2.65 ± 1.55 min in the IPIA group (p = 0.002), without statistical significance of expenses. Conclusion: IPIA was demonstrated to be as safe and effective as conventional antiseptic solutions as a skin preparation to prevent SSI following colorectal surgery. With good ease of use, IPIA proved more convenient than a scrubbing preparation as well as offered better cost effectiveness by significantly reducing the time and cost of the skin preparation.